Controllable Synthesis and Surface Modifications of a Metastable O2-Type Li-Rich Cathode Material - Yiming Sun; Junjie Huang; Hongzhou Zhang; Lianqi Zhang; Defa Wang (Crystals, 2023)
Li-rich materials have become one of the most promising cathode candidates for next-generation lithium-ion battery systems due to their high capacity and operating voltage. Conventional O3-type Li-rich materials undergo a structural transition from a layered to a spinel phase during cycling, leading to the degradation in their electrochemical performance, especially in terms of their voltage decay. The oxygen atoms comprising the structure of O2-type Li-rich materials are stacked in the ABAC configuration, which can effectively suppress these harmful phase transitions. However, O2-type Li-rich materials are metastable structures and can only be synthesized via the means of complex ion exchange methods. In addition, the surface of the material is susceptible to side reactions with the electrolyte when charged to high voltages. Here, we explored the optimal conditions for the synthesis of O2-type Li[Li0.25Ni0.1Co0.05Mn0.6]O2 (LLNCM) in more detail by preparing the precursors using the sol-gel method. Meanwhile, the modification of the material’s surface via low-temperature hydrolysis of aluminum isopropoxide has been proposed for the first time in this study to avoid the damage of metastable materials by the high-temperature coating process. The surface-modified materials prepared under optimal conditions exhibited an excellent electrochemical performance, indicating that a highly stable O2-type bulk phase structure with effective surface modification is a potential way to promote the commercial applications of Li-rich cathode materials.